Investigation of the D ({3}He, p) {4}He reaction as an alternative for the T (D, n) {4}He reaction in the production of thermonuclear energy; Энерго-ресурсоэффективность в интересах устойчивого развития - Bystritsk V. M.; Dudkin G. N. Gennadiy Nikolaevich; Chumakov D. K.; Filipowicz M.; Filippov A. V. Andrey Vladimirovich; Krylov A. R.; Nechaev B. A. Boris Aleksandrovich; Nurkin А. Azamat; Padalko V. N. Vladimir Nikolaevich; Penkov P. G. Paul Gennadievich; Tuleushev Yu. Zh.; Varlachev V. A. Valery Aleksandrovich; et al. (Теоретические основы повышения энергетической эффективности, 2018)
Заглавие с экрана